Skenario Target Indeks Pembangunan Manusia Kabupaten Tabalong dan Kabupaten Hulu Sungai Utara Tahun 2024-2028 - Nazmi, Haliza; Muttaqin, Hidayatullah (PPJP ULM, 2025)
This study aims to develop Human Development Index (HDI) targets in Tabalong and Hulu Sungai Utara (HSU) districts from 2024 to 2028 under Optimistic, Moderate, and Pessimistic scenarios. Using HDI data and HDI components, and applying linear projection and average increase models. The HDI simulation used the ADIM South Kalimantan application from Bappeda of South Kalimantan Province. The results of the analysis of the HDI target of Tabalong Regency in 2024 for the Optimistic, Moderate and Pessimistic scenarios are: 74.74; 74.61; 74.49 and 2028 rose to: 77,15; 77,02; 76,90. Similarly, for HSU District, the HDI targets in 2024 were 68.74; 68.61; 68.49 and 2028 increased to 71.55; 71.42; 71.30. The simulation of HDI components shows the need for measurable and data-based targets to avoid targets that are too high or low from regional potential.